Finance and Organization: The Implications for Whole Farm Risk Management - Michael Friis Pedersen (Copenhagen Business School (CBS), 2013)
This thesis analyzes the institutional framework around risk management in Danish agriculture, with the two main sectors, the hog and the dairy sector in mind, and it suggests a new more active role for the cooperatives in these sectors, with regard to the reallocation of price risk among members. The thesis consists of a general introduction, three linked but independent and self-contained papers and a conclusion. The first paper introduces a measure of credit capacity using Data Envelopment Analysis. This is a novel application of a well-known methodology from production economics on financial issues. The paper was motivated by the fact that most literature on risk management explains the rationale for risk management activities such as hedging, with increased ability to obtain finance via debt. However, no hedging had been performed on the output side for Danish pig or dairy farms, while access to debt capital seemed abundant. It seemed that farmers may have been thinking “Why hedge, if you can borrow?” The perception of the abundant availability of liquidity in the form of credit reserves may have been an explanation for the absence of other risk management activities in the sectors and why a measure and empirical analysis of the development in credit capacity was needed. However, existing measures of access to credit had focused on the dichotomous question of whether firms are financially constrained or not, while the relative unconstrainedness of firms (farms) would have explained the absence of risk management. An analysis of some 92,000 farm accounts from 1996 to 2009 found that access to credit roughly doubled during the period. This may have been an important explaining factor for the (absent) development of risk management institutions.
hdl:10398/8817
Keywords: 650